2019
DOI: 10.3892/mmr.2019.10032
|View full text |Cite
|
Sign up to set email alerts
|

circEIF4G2 modulates the malignant features of cervical cancer via the miR‑218/HOXA1 pathway

Abstract: Circular RNAs (circRNAs) serve important roles in tumorigenesis and may be used as novel molecular biomarkers for clinical diagnosis. However, the role and molecular mechanisms of circRNAs in cervical cancer (CC) remain unknown. In the present study, circRNA isoform of eukaryotic translation initiation factor 4γ2 (circEIF4G2) was revealed to be significantly upregulated in CC tissues and cell lines. Furthermore, increased expression of circEIF4G2 was associated with poor prognosis in patients with CC. circEIF4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 28 publications
(23 reference statements)
1
33
0
Order By: Relevance
“…In OS, knockdown of EIF4G2 significantly decreased translation and cell proliferation and induced cellular senescence [20]. The circRNA isoform of EIF4G2 was found to be upregulated in cervical cancer (CC) [29]. The molecular function studies demonstrated that circEIF4G2 acted as an oncogene in CC by promoting cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In OS, knockdown of EIF4G2 significantly decreased translation and cell proliferation and induced cellular senescence [20]. The circRNA isoform of EIF4G2 was found to be upregulated in cervical cancer (CC) [29]. The molecular function studies demonstrated that circEIF4G2 acted as an oncogene in CC by promoting cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…14 Mao et al revealed that circEIF4G2 promoted the malignant features of CC through regulating the miR-218/HOXA1 axis. 15 Tian et al found that circSMARCA5 inhibited the proliferation and invasion in CC by regulating miR-620. 16 In the current study, we analyzed the GSE102686 chip and found hsa_circ_0008285 was one of the most upregulated circRNAs, which was further explored in CC tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway controls multiple cellular processes including proliferation, growth, invasion and chemoresistance, and it is one of the most frequently dysregulated pathways in human cancers, including CC [106,107]. Integrin β1 can promote cancer initiation and progression through the activation of multiple downstream pathways, including the PI3K/AKT Diverse circRNAs (such as circEIF4G2, circ0007534, circ0005576, circ0075341, circ0000515, circAMOTL1, and circSLC26A4) were previously described to promote the tumorigenesis of CC by increasing the respective downstream targets mRNAs, including HOXA1, BMI-1, KIF20A, AURKA, ELK1, AMOTL1 and HOXA7 via sponging miRNAs [84,90,91,94,95,97,101]. Additionally, circRNAs (such as circ0018289, circ0000285 and circMYBL2,) were found to be overexpressed in CC tissues, and their upregulation enhanced CC cell invasion and metastasis [76,92,98].…”
Section: Circrnas In CCmentioning
confidence: 99%